Status wanita dalam undang-undang jenayah Islam - Paizah Hj.Ismail, 1947- (Kuala Lumpur : YADIM, 2004)
Status of women in Islamic criminal law
Bibliografi: p. 269-276
Keywords: Criminal law (Islamic law); Women -- Legal status, laws, etc. (Islamic law); Women in Islam; Women -- Religious aspects -- Islam